Comparative effects of arithmetic, speech, and motor dual-task walking on gait in stroke survivors: a cross-sectional study - Xueyi Zhang; Xueyi Zhang; Qi Wang; Qiujie Li; Qiujie Li; Hui Liu; Hui Liu; Xianglin Wan; Xianglin Wan (Frontiers in Human Neuroscience)
BackgroundThe application of dual-task walking paradigms for gait assessment in stroke patients is critical, where varying concurrent tasks may elicit distinct gait patterns of dual-task interference. This study assessed the acute effects of different types of dual tasks on gait in stroke patients during task performance, informing occupational, and physical therapists about care recommendations to prevent patients from falling and improve their balance function in daily life.MethodsA total of 19 stroke patients (52.7 ± 6.9 years old) performed the walking-only and dual-task walking (motor, arithmetic and speech) task test while a 3D motion capture system measured the gait parameters (the gait spatial-temporal parameters, sagittal angle of lower-limb joints, gait parameter variability and dual-task cost). One-way repeated measures ANOVA was used to test the effects of the above four walking conditions on gait parameters.ResultsArithmetic task and speech task interference can affect the gait of stroke patients (P < 0.05). Arithmetic task interference has the greatest impact on step speed, cadence, single support phase, hip joint range in support period and has the greatest dual-task cost, speech task interference has the greatest impact on cadence coefficient of variation (P < 0.05). The motor task was not significantly different from walking-only (P >0.05).ConclusionBoth arithmetic and speech tasks have a great impact on gait in stroke patients. Faced with cognitive interference, stroke patients spontaneously adopted a “cautious gait” walking pattern. In future rehabilitation training, diversity of task types is critical for gait rehabilitation training based on the walking ability of the patients.